Implementation of the Authority of Consumer Dispute Resolution Agency in Presenting Business Actors With the Assistance of Police Investigators - Putri, Aulia Cahyono (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The Consumer Dispute Resolution Agency has the authority to request the assistance of investigators in presenting business actors as stipulated in the Consumer Protection Law.Purposes of the Research: Analyzing why business actors are not present in the dispute resolution process, then settlement efforts through the Consumer Dispute Resolution Agency cannot be continued.Methods of the Research: This study uses a juridical-empirical method with data collection techniques through interviews, documentation, and literature studies.Findings of the Research: The results of the study show that the Yogyakarta Consumer Dispute Resolution Agency basically has the legal authority to present business actors forcibly with the help of investigators if the business actors are not present voluntarily. However, in practice, this authority has never been used, and is even considered unenforceable. The main obstacle in the implementation of this authority lies in the legal factors themselves, especially the unclear legal norms regarding the scope of the role of investigators in the context of consumer disputes. In addition, although the authority of the Consumer Dispute Resolution Agency has been normatively regulated in law, the investigator does not have any technical guidelines or implementing rules that are the basis for following up on requests from the Consumer Dispute Resolution Agency.